The psycholinguistics of propaganda: mechanisms of subjugation and how to challenge them - Isacoff, Nora M. (East European Journal of Psycholinguistics, 2022)
This paper reviews current research on the oppressive and dehumanizing use of language by those in political power to promote essentialist thought about oppositional groups, including during the war in Ukraine. Essentialism is the implicit belief that categories of people–those of certain ethnicities or nationalities, for example–have intrinsic, immutable properties, driven by some deep, unobservable, and often deterministic causal essence. There is robust evidence that cross-culturally, both young children and adults sometimes employ an essentialist heuristic when reasoning about cultural traits, and that they see others’ traits as being less mutable than their own. Strikingly, though, cultures vary drastically in the particulars and extent of this cultural essentialism. Thus, it seems clear that cultural input can to some degree either exploit or overwrite a tendency toward cultural essentialism, with language being an especially powerful mechanism. In this paper, I demonstrate ways that language is intentionally used by those with political power to promote essentialist thought and to justify violence. In particular, I highlight use of generic language, ascriptive definitions, and the language of opposites within propaganda. I end with consideration of ways to be responsive to instances of propaganda within our own communities and as global citizens, such as through pro-social repurposing of the linguistic tools that have been used destructively, promoting nuance through the use of differentiated language, and by capitalizing on an intuitive human belief in essential goodness and desire for truth. Acknowledgements Deepest gratitude to Alexander Barhavin for translating the abstract from English into Ukrainian.